Applied Physiology in Intensive Care Medicine 1 2012
DOI: 10.1007/978-3-642-28270-6_61
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and microcirculatory responses to progressive hemorrhage

Abstract: A. Dubin ( ) ) calle 42 No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Only those parameters who were significant are given PLR passive leg raising, VE volume expansion, NS non-significant, HR heart rate, MAP mean arterial pressure, CO cardiac output, SV stroke volume, DPP respiratory variation in arterial pulse pressure, ANOVA analysis of variance * P \ 0.001 versus Baseline 1 and Baseline 2 § P \ 0.001 versus PLR à P \ 0.001 versus VE DPP = PLR investigated, MFI is known to be rather sensitive to flow variations, while FCD and PPV are more directed towards recruitment of the microcirculation. This opposite relationship between changes in MFI or PPV and changes in heterogeneity is in accordance with the results of an experimental study [20] in which animals were bled, thus producing effects in the opposite direction in comparison with those of our study. To the best of our knowledge, these results have not yet been reported in the clinical setting.…”
Section: Discussionsupporting
confidence: 81%
“…Only those parameters who were significant are given PLR passive leg raising, VE volume expansion, NS non-significant, HR heart rate, MAP mean arterial pressure, CO cardiac output, SV stroke volume, DPP respiratory variation in arterial pulse pressure, ANOVA analysis of variance * P \ 0.001 versus Baseline 1 and Baseline 2 § P \ 0.001 versus PLR à P \ 0.001 versus VE DPP = PLR investigated, MFI is known to be rather sensitive to flow variations, while FCD and PPV are more directed towards recruitment of the microcirculation. This opposite relationship between changes in MFI or PPV and changes in heterogeneity is in accordance with the results of an experimental study [20] in which animals were bled, thus producing effects in the opposite direction in comparison with those of our study. To the best of our knowledge, these results have not yet been reported in the clinical setting.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, we found that, with heterogeneous impairment of microcirculatory blood flow intensity within the intestine, the mucosa was more susceptible to hemorrhaging than the serosal muscular layer and Peyer's patch. Similarly, Dubin et al used SDF imaging in a sheep model of hemorrhagic shock and found that greater decreases in capillary density and increases in heterogeneity, implying a higher susceptibility to hemorrhaging, occurred in the ileal mucosa than in the ileal serosa and sublingual mucosa (Dubin et al, 2009). However, other splanchnic organs were not compared in that report.…”
Section: Discussionmentioning
confidence: 95%
“…Both macrocirculatory and microcirculatory dysfunctions have been characterized in the acute phase of hemorrhagic shock (Dubin et al, 2009;van Iterson et al, 2012). Recently, there is a paradigm shift from macrocirculatory to microcirculatory investigations because the persistence of microcirculatory dysfunction is associated with organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…In hemorrhagic shock, an important part of the microvascular alterations appears to be closely related to macrocirculatory variables (i.e., CI and oxygen delivery) (17,18). A progressive decrease in cardiac output and oxygen delivery induces a progressive decrease in the capillary blood flow, RBC velocities, and FCD, with an increase in flow heterogeneity (19,20). These microvascular alterations are more pronounced in nonvital organ microcirculations (splanchnic, renal, and musculocutaneous microcirculations) and in microvascular units with low oxygen demands and nonessential cell functions.…”
Section: Discussionmentioning
confidence: 99%